SELF-EFFICACY IN CLINICAL TEACHING AMONG NURSES AND ASSOCIATED FACTORS AT NAM DINH UNIVERSITY OF NURSING IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the confidence levels of nurses in clinical teaching for nursing learners at practice settings and to identify associated factors.Methods: A cross-sectional descriptive study was conducted on 400 nurses serving as visiting lecturers at Nam Dinh University of Nursing from January 2025 to June 2025. Data were collected online using the self-efficacy in teaching tool - nursing education.Results: Among the 400 participants, the majority were married (68.3%). Regarding educational attainment, those with a bachelor’s degree accounted for the highest proportion (46%). Most subjects were working in the public health sector (91.3%), with the majority employed at the provincial level (58%). In terms of professional roles, department head nurses comprised the largest group (40.8%). The confidence levels of the nurses were predominantly average (44.5%) and low (37%), while only 18.5% reached a high level. Significant associations were found between general characteristics and clinical teaching confidence. Specifically, high confidence was more prevalent among those aged over 51, females, PhD holders, those with 5-10 years of work experience, those working at central-level facilities, and hospital chief nursing officers.Conclusion: The confidence level of nurses in clinical teaching was mainly at an average-to-low level and was significantly associated with educational level, healthcare tier, and professional position.
Keywords: Self-efficacy, clinical teaching, nurses, nursing educators.